Hematopoietic stem cell development and regulatory signaling in zebrafish - Zhang, C; Patient, R; Liu, F (2013)
Background: Hematopoietic stem cells (HSCs) are a population of multipotent cells that can self-renew and differentiate into all blood lineages. HSC development must be tightly controlled from cell fate determination to self-maintenance during adulthood. This involves a panel of important developmental signaling pathways and other factors which act synergistically within the HSC population and/or in the HSC niche. Genetically conserved processes of HSC development plus many other developmental advantages make the zebrafish an ideal model organism to elucidate the regulatory mechanisms underlying HSC programming. Scope of review: This review summarizes recent progress on zebrafish HSCs with particular focus on how developmental signaling controls hemogenic endothelium-derived HSC development. We also describe the interaction of different signaling pathways during these processes. Major conclusions: The hematopoietic stem cell system is a paradigm for stem cell studies. Use of the zebrafish model to study signaling regulation of HSCs in vivo has resulted in a great deal of information concerning HSC biology in vertebrates. General significance: These new findings facilitate a better understanding of molecular mechanisms of HSC programming, and will provide possible new strategies for the treatment of HSC-related hematological diseases, such as leukemia. This article is part of a Special Issue entitled Biochemistry of Stem Cells. © 2012 Elsevier B.V.